2021
DOI: 10.12688/f1000research.52383.1
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon extract effects on insulin resistance, metabolic factors, and menstrual cyclicity of women with polycystic ovary syndrome: A systematic review and meta-analysis

Abstract: Background: Cinnamon is a herbal medicine that is supposed to improve the metabolic disorder polycystic ovary syndrome (PCOS), but there is still no data about the effectiveness and efficacy of this herbal medicine for the metabolic parameters of PCOS. This study aims to systematically evaluate the effects of cinnamon extract on improving insulin resistance, lipid profile and regularity of menstruation in PCOS women. Methods: This is a systematic review and meta-analysis of randomized controlled trials (RCTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…[ 108 , 109 ] Another study explored cinnamon extract (a traditional herb), as it has been shown to potentiate the insulin effect through the upregulation of glucose uptake in cultured adipocytes. [ 110 , 111 ] The use of supplements, including omega-3 and vitamin E, due to improved insulin sensitivity and inflammation, remains the most effective treatment strategy for PCOS subjects. [ 112 ] Omega-3 and vitamin E co-supplementation effectively enhance mental health parameters and gene expression of PPAR-γ, IL-8, and TNF-α in women with PCOS.…”
Section: Managementmentioning
confidence: 99%
“…[ 108 , 109 ] Another study explored cinnamon extract (a traditional herb), as it has been shown to potentiate the insulin effect through the upregulation of glucose uptake in cultured adipocytes. [ 110 , 111 ] The use of supplements, including omega-3 and vitamin E, due to improved insulin sensitivity and inflammation, remains the most effective treatment strategy for PCOS subjects. [ 112 ] Omega-3 and vitamin E co-supplementation effectively enhance mental health parameters and gene expression of PPAR-γ, IL-8, and TNF-α in women with PCOS.…”
Section: Managementmentioning
confidence: 99%